2021
DOI: 10.1002/hec.4256
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid expansion and the mental health of college students

Abstract: Reported mental health problems have risen dramatically among US college students over time, as has treatment for these problems. We examine the effect of state-level Medicaid expansion following the 2014 implementation of the Affordable Care Act on the diagnosis of mental health conditions, psychotropic prescription drug use, and the mental health status of a national sample of college students. We find that students from disadvantaged backgrounds are more likely to report being on public insurance after 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
1
14
0
Order By: Relevance
“…It temporarily interferes with or disrupts one's habitual pattern of life, characterized by high levels of tension, accompanied by anxiety, frustration, and confusion. e psychological crisis of college students can lead to behavioral or emotional disorders and even lead selfinjury or injury and other serious consequences [7]. But people's psychological problems from the emergence to the degree of serious need to go through a gradual development process; if the problem in this process is resolved or alleviated, then the tragedy may not occur [8].…”
Section: Introductionmentioning
confidence: 99%
“…It temporarily interferes with or disrupts one's habitual pattern of life, characterized by high levels of tension, accompanied by anxiety, frustration, and confusion. e psychological crisis of college students can lead to behavioral or emotional disorders and even lead selfinjury or injury and other serious consequences [7]. But people's psychological problems from the emergence to the degree of serious need to go through a gradual development process; if the problem in this process is resolved or alleviated, then the tragedy may not occur [8].…”
Section: Introductionmentioning
confidence: 99%
“…The expansions also extended coverage to low‐income, childless adults, a group historically not eligible for the program. Early work has found that ACA Medicaid expansion led to significant insurance coverage gains among those living in newly expanding states (Buchmueller et al., 2019; Courtemanche et al., 2017; Cowan & Hao, 2021). If marriage leads to Medicaid ineligibility for an individual living in a newly expanding state, it is plausible that Medicaid expansion leads to a greater share of individuals avoiding marriage or getting divorced after 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Psychological pressure is a state of mental and physical tension that individuals tend to show through various psychological and physiological reactions when they perceive or recognize that they are facing the important and difficult environmental requirements [1][2][3]. High-efficiency life has inevitably brought people a sense of urgency and pressure, and the mental health problems of college students have become increasingly prominent [4,5]. Due to a series of problems, such as academic, interpersonal, emotional, and job competition, college students are prone to negative emotions, such as inferiority, jealousy, depression, irritability, anxiety and fear, and even violent tendencies, which will cause serious harm to themselves and even society in the long run.…”
Section: Introductionmentioning
confidence: 99%